STRATEGI PENGEMBANGAN POTENSI WISATA ALAM GUNUNG TELETUBIS DI DESA GILILANA KABUPATEN MOROWALI UTARA - Maysita, Fanny; Sudhartono, Arief (Universitas Tadulako, 2020)
Petasia District is one of the districts in North Morowali Regency which has a wealth of tourism potential and natural resources that are plagued, one of which is Mount Teletubis located in Gililana Village. The formulation of the problem to be discussed is how the Development Strategy of Mount Teletubis Natural Tourism Potential in Gililana Village. This research was conducted from May to June 2019 in Gililana Village, North Morowali Regency, Central Sulawesi Province. This study used descriptive qualitative method. The procedure of conducting research and data collection is direct observation, interviews and also the collection of documentation. The analysis used in this research is SWOT Analysis. Potential Development Strategies of Mount Teletubis Nature Tourism namely: Developing the potential of tourist objects and attractions namely culinary and arts and cultural tourism, giving guidance to the surrounding community regarding the need to preserve the original culture that has become a cultural tourism destination in the Mount Teletubis natural tourism area, held by Art and Culture in the tourist area so that the community and tourists know the importance of preserving the culture in Gililana Village, fostering the community as a tour guide and community economic development. the manager has to empower the people around the tourism area so there is good cooperation between the community and the management, in this case the North Morowali Regency Tourism and Arts Office.Keyword : Gunung Teletubis, Wisata Alam,Masyarakat.